Body-Part Terms and Emotions: Latin pectus in Ovid’s Poetry - Kochovska-Stevovikj, Svetlana (University Library, Belgrade, 2019)
The aim of the paper is to explore the conceptualizations of Latin pectus ‘chest’, ‘breast’ in Ovid. As evidenced by many pectus-expressions, the chest is conceived as a container in which an infinite set of ‘things’ can be stored: senses, breathing channels and breath, voice and speaking abilities, emotions and feelings, memories, thoughts and mind. Some of the functions that are associated with pectus are physiological in the strict sense (e.g. physiological perception, breathing, sleeping and voice production), some, as emotions, have both physiological and cognitive components, and some are exclusively cognitive. Each of the physiological functions is dependent on specific things imagined as being in or outside the chest: falling asleep, for instance, is understood as a condition in which the sleep holds the chest (somnus pectora habere), and awakening as a condition in which the sleep is departed from the chest (somnus abesse a pectore). Emotions and feelings are mainly described as external forces that can be inside or outside one’s chest. Whenever they are inside the chest, they have an influence on its temperature and on its weight (amor in pectore flagrare, pectora flagrant odio etc.). Unpleasant feelings, such as worries, are perceived as a weight on one’s chest (onerare pectora); the relief from the worries, accordingly, is viewed as a condition in which the chest is relieved from the weight (relevare pectora). Personality traits are also conceived as being related to the chest: cruelty, for instance, is described as a trait dependent on the things contained inside one’s chest (habere silices et vivum ferrum in pectore). As a figurative locus of thought and memories, the chest is conceived as a body part responsible for reasoning, thinking and remembering. A person who is described as being toto pectore captus (lit. ‘caught in the whole chest’) is actually a person whose mental capacities are reduced to the point that he is not able to reason. In Ovid’s poetry the noun pectus metonymically stands for a person’s feelings, thoughts and mind, as well as for a person as a whole. These metonymic extensions are motivated by the conceptual metonymies CONTAINER FOR CONTAINED and PART FOR WHOLE.
Keywords: body-part terms, Latin pectus, emotions, Ovid